Nano-vectors for CRISPR/Cas9-mediated genome editing. (June 2022) - Yang, Peng; Lee, Athena Yue-Tung; Xue, Jingjing; Chou, Shih-Jie; Lee, Calvin; Tseng, Patrick; Zhang, Tiffany X.; Zhu, Yazhen; Lee, Junseok; Chiou, Shih-Hwa; Tseng, Hsian-Rong
Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (CRISPR/Cas9) genome editing system has revolutionized the field of genome editing for therapeutic applications for genetic diseases and cancers, the development of disease models, identification of targets for drug development. However, safe and efficient delivery of the CRISPR/Cas9 genome editing system in vivo remains a significant challenge. Compared to viral vectors, non-viral nano-vectors have the following advantages: cost-effective, scale-up production, ease of chemical modification, large packaging capacity, lower immunogenicity, better protection of CRISPR/Cas9 genome edition system from degradation in vivo. This comprehensive Review article highlights the recent advances in delivering the three categories of CRISPR/Cas9 genome editing cargoes (i.e., Cas9 DNA plasmid, Cas9 mRNA, and Cas9 ribonucleoprotein) by using three types of nano-vectors: lipid-based, polymer-based, and polymer inorganic nano-vectors to treat cancers and genetic diseases via two major gene-editing pathways: non-homologous end joining pathway and homology-directed repair pathway. This article also notes the therapeutic applications for treating cancers and genetic diseases, provides insights into the challenges of nano-vectors for the delivery of the CRISPR/Cas9 genome editing system and proposes promising strategies in future development, especially in the final clinical translation. Graphical Abstract: We report recent advances in non-viral nano-vector delivery of the CRISPR/Cas9 genome editing payloads (i.e., Cas9 DNA plasmid, Cas9 mRNA, and Cas9 RNP), showing as potential therapeutic applications for treating cancers and genetic diseases via systemic or local administration into organs, such as brain, eye, lung, liver, muscle, and tumor. ga1 Highlights: Recent advances in non-viral nano-vector delivery of the CRISPR/Cas9 genome editing payloads is comprehensively reviewed. Lipid, polymer, or inorganic composition are typical examples of nano-vectors. Nano-vectors can deliver three different payloads including plasmid, mRNA, and RNP for CRISPR/Cas9 genome editing. More research is expected to explore the next-generation nano-vectors.